Promotive and preventive programs of heavy infection knowledge in Medan Barat district - Lubis, Bastian; Amelia, Putri; Akil, Muhammad (Talenta Publisher, 2019)
Sepsis is still an important health problem in the world today. The incidence of sepsis can reach 750,000 cases per year. When mothers have a vital role in family health, their lack of knowledge and concern about sepsis remains an obstacle. Therefore, we need a program to promote and prevent sepsis among mothers in West Medan District as an effort to reduce the number of sepsis in Indonesia. Coaching, training, and counseling are given to PKK mothers and Posyandu cadres regarding the prevention of severe infections that can cause sepsis. This activity began by collecting basic data using the Sepsis Knowledge Scale questionnaire and then provided counseling and training on sepsis. Then, the final results were assessed with a behavioral questionnaire and sepsis knowledge questionnaire. The activity was attended by 29 people, 20 women (72.4%) and 9 men (27.6%). No significant changes were found in the level of knowledge and behavior before and after the activity (Z-score: 0.001; p = 1,000).